Estudio de factibilidad para la creación de una empresa productora, envasadora y comercializadora de licores de sabores en la ciudad de Guaranda, como un medio de atractivo turístico. - Guadalupe García, Luz Estefanía (2014)
This study reports an analysis made of the best alternative would be creating a producer, packer in Guaranda flavored liqueurs, as a means of attraction, to potentiate the traditions that identify this beautiful city such as the different types of drinks including liquors more traditional flavors with an added value in terms of taste, given that will occur based on typical fruits tropical sector of the Province of Bolivar. With respect to market analysis we highlight the analysis carried out in order to know the preferences of our potential market, taking into account the population of Guaranda, disaggregating the sample of those being over 18 years old may consume our spirits, watching the tastes and preferences, frequency of consumption and the value that would be willing to pay for flavored liqueurs that would occur. The technical study analyzed all the factors that determine the location , real and installed capacity of the project, this allowed us to have a broader view of how many units of alcohol would produce monthly and annual basis in order to justify the value that we would invest for this item .